Simulation Analysis and Experimental Study of the Automobile Synchronous Belt Drive Noise - Shi Yaochen; Li Zhanguo; Li Shuiqing; Zhao Xilu (Jixie chuandong)
A finite element analysis model of the ZA synchronous belt drive system is established. Through the finite element method,the natural frequency of the automobile synchronous belt and its dynamic response under the action of meshing impact excitation are analyzed. And based on the dynamic response results,the acoustic boundary element analysis model of the transmission system of the automobile synchronous belt is established by the direct boundary element method,the influence law of meshing excitation frequency on the synchronous belt surface sound pressure and field radiated noise is analyzed. The noise test of the synchronous belt drive system is carried out by using two wheel load test method. Comparison of the radiated noise and the numerical simulation results,the accuracy and feasibility of the simulation method is verified.